Life and Literary Personality of Esat Erbil, One of the Iraqi Turkmen Poets - Hakary Qasm Baez (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In this study, the 20th-degree study of Iraqi Turkmen Literature. The theme will be examined in the poems of erbil poet Esat Erbil, one of the representatives of the 20th century. Although the poet, who wrote poetry in all styles and has an important place in Erbil, as well as in Kurdistan. is an important literary figure in Iraqi Turkmen Literature, there has not been enough and extensive work done on him before. Therefore, in order to better know and understand the poet and his poetry, a neat and disciplined study of his life, personality and poetry was required. During this study, resource scanning method, one-to-one interview and interview methods were used with the poet. The poet's life, family, environment, influence, recognition and works are discussed in independent titles. All his poems published in books and not in his books have been translated into modern Turkish by transcription method. In addition, the words of the folk language and Erbil region found in the poems are explained. The transcript, index and provided documents of the poet's poems are given in this study.